Media credibility and its correlate with popular votes during elections - Syed Abdullah Idid, Syed Arabi; Wok, Saodah (2005)
Researchers have been concerned with media credibility on several counts. One is the concern of media effects on the audience. The reasoning is that the more credible the media, the more effects the media are said to have on the audience. Media credibility is the degree of believability of the source of information by the audience. This paper presents a longitudinal study on media credibility and relates the concept of media credibility to popular votes obtained during the general Malaysian elections. This paper traces the degree of credibility of two major media, newspaper and television. Specifically the paper has two main objectives, namely to gauge the level of media credibility over a period of time, and to analyze the changing credibility level of the specific media to the popular votes obtained during the general elections.